Quality of Systems and Information in the Use of Electronic Medical Records at Santa Elisabeth Hospital - Simbolon, Pomarida (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
The use of electronic medical records with quality information systems greatly influences the achievement of work results or what is often referred to as performance. The higher the satisfaction with using electronic medical records, the higher the quality of the information system. The quality of an information system is a measure of the information system itself and how great the technology is in computer systems it is felt that it is relatively easy to use and does not require a lot of effort to get it done use it.The aim of the research is to identify an overview of the quality of the system and information in the use of electronic medical records in the Inpatient Room at Santa Elisabeth Hospital, Medan in 2023. This type of research is descriptive. The sample in the study consisted of 40 respondents using a proportional stratified random sampling technique. Data collection was carried out using a questionnaire. Data were analyzed univariately. The results of this research showed that 21 people (52.5%) had less system and information quality. It is hoped that Santa Elisabeth Medan Hospital can improve the quality of the electronic medical record application so that the use of electronic medical records is even better.